Physical activity and mental health; it is more than just a prescription - Rebar, Amanda; Taylor, A. (Elsevier BV, 2017)
Â© 2017 Elsevier Ltd Most mental health and physical activity research describes unidirectional causes of physical activity on mental health, and as a result, a strong evidence base is being established for the effectiveness of physical activity as a treatment for mental health issues. Given that the efficacy of physical activity prescriptions are entirely reliant on individualsâ€™ behavioral engagement, the aim of this special issue is to draw attention to translational evidence relevant to mental health and physical activity. This issue encompasses findings from a wide array of study designs (e.g., reviews, qualitative investigations, correlations studies, trial descriptions, pilot trial findings) of populations from high, middle, and low-income countries with clinical and non-clinical mental health issues. The evidence illustrates that people with mental health issues have unique facilitators and barriers to physical activity that are not accounted for within behavior change theories or interventions for the general population. Within this issue, you will find evidence of how mental health issues impact physical activity behavior change processes as well as examples of how context and person factors may moderate physical activity intervention efficacy amongst these populations. Informed by this evidence, we are calling for future research to investigate acceptability, maintenance, scalability, and generalizability of physical activity interventions for people with mental health issues. This future research will need to account for the unique barriers and facilitators of the population, be theoretically sound, apply to unique contexts, and adapt to dynamic change processes (including engagement and maintenance).